PELATIHAN PEMBELAJARAN LITERASI-NUMERASI BERBANTUAN TEKNOLOGI DAN AI BAGI GURU SD DI MADIUN - Jeffry Handhika; Joel Iglesia Alvarez; Tantri Mayasari; Nugroho Adi Pramono; Sarah Aszary; Sri Winarti (Jurnal Terapan Abdimas, 2026)
Abstract. The purpose of this community service activity, in the form of training, is to provide knowledge and skills to participants, specifically teachers, related to integrated literacy and numeracy learning using technology and artificial intelligence (AI). This activity method is carried out in the form of blended meetings and assignments. The indicator of success of this activity is an increase in participants' desire to apply integrated literacy, numeracy, and technology (LNAI) learning in learning. There are four facilitators involved in this activity; one facilitator explains the material delivered in a blended manner. The training participants were 93 madrasah teachers in the city of Madiun. After the training activity, information was obtained that there was an increase in participants' desire to apply LNAI learning from 49.5% who had implemented it to 66.57% who would implement it, 33.33% who might implement it, and 0% who did not implement it. These results provide the conclusion that there is potential for increasing the application of LNAI in learning.   Abstrak. Tujuan kegiatan pengabdian masyarakat dalam bentuk pelatihan ini adalah untuk memberikan pengetahuan dan keterampilan bagi peserta dalam hal ini guru terkait pembelajaran literasi dan numerasi terintegrasi teknologi dan artificial intelligence (AI). Metode kegiatan ini dilakukan dalam bentuk pertemuan secara blended dan penugasan. Indikator keberhasilan dari kegiatan ini adalah adanya peningkatan keinginan peserta untuk menerapkan pembelajaran literasi, numerasi terintegrasi teknologi dan AI (LNAI) dalam pembelajaran. Terdapat empat fasilitator yang terlibat dalam kegiatan ini, satu fasilitator menjelaskan materi yang disampaikan secara blended. Peserta pelatihan diikuti oleh 93 guru madrasah di kota Madiun. Setelah kegiatan pelatihan, diperoleh informasi bahwa terdapat peningkatan keinginan peserta dalam menerapkan pembelajaran LNAI dari 49,5% pernah menerapkan menjadi 66,57% akan menerapkan, mungkin menerapkan 33,33% dan tidak menerapkan 0%. Hasil ini memberikan kesimpulan bahwa terdapat potensi peningkatan penerapan LNAI dalam pembelajaran.